A CASE OF PLEOMORPHIC ADENOMA ORIGINATING FROM THE NASAL SEPTUM - Tsunemi, Yasuhiro; Miyashita, Keisuke; Hirabayashi, Hideki; Tanaka, Yasuhiro; Kashiwagi, Takashi; Haruna, Shin-ichi; Akutsu, Makoto; Kanaya, Hiroaki; Aoki, Satoshi (JIBI INKOKA TEMBO, 2019)
We encountered a case of pleomorphic adenoma originating from the nasal septum. A 67-year-old male was referred to our institution by a physician for further evaluation of a right intranasal mass. The patient complained of right-sided nasal obstruction and serous nasal discharge. Computed tomographic images showed a localized tumor arising from the nasal septum. Endoscopic endonasal surgery was performed for resection of the tumor and the tumor was completely removed without adhesion to the nasal septal cartilage or to the perpendicular plate of the ethmoid bone. The final histological diagnosis was typical pleomorphic adenoma. The patient was followed up at our outpatient clinic and did not show any evidence of recurrence.　In general, pleomorphic adenoma is a benign epithelial tumor and is associated with a favorable clinical course. Although major salivary glands, such as the parotid and submandibular glands are the most frequently affected sites, this tumor sometimes arises from the minor salivary glands in the nasal cavity or palate. For surgical treatment, en-bloc resection of these lesions is strongly recommended because of the possibility of malignant transformation. Careful follow-up of the patient is also vital to check for disease recurrence.